Efficient Route Planning for Flour Distribution: A Heuristic Approach - Baisa, Said Muhammad; Imran, Arif; Maulana, Hilman; Afifah, Alif Ulfa (Jurnal Sistem Teknik Industri, 2024)
This company operates in the Food and Beverage sector, selling Martabak, an Indonesian snack. The company needs to deliver flour to 25 branches spread across Bandung, Indonesia, every day, with varying demand capacities at each branch. Each day, the total amount of flour to be delivered is 377 boxes. Currently, the company has 12 distribution routes with a total distance of 271,16 km, with each route covering only two stores. However, these routes are too many and vehicle capacities need to be optimized, resulting in a high total travelled distance. The aim of this research is to optimize the delivery routes to reduce the total travelled distance and number of routes. To address this issue, known as the Vehicle Routing Problem (VRP), heuristic methods were employed, specifically the nearest neighbour method for initial route construction and Intra-Route (1-0) Insertion for improvement. Implementing these heuristic methods resulted in a final total of 6 distribution routes with a total distance of 160,90 km. This method successfully reduced the total travelled distance by 110,26 km and reduced the number of routes by 6. In conclusion, the application of heuristic methods in solving the VRP for this company proved to be effective in reducing both the total travelled distance and the number of routes, thereby enhancing the operational efficiency of the delivery process.